1971
DOI: 10.1159/000259747
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Ion Activity in vitro and in vivo of Two Sodium Fluoride Dentifrices

Abstract: The fluoride ion activities of two NaF dentrifrices have been determined in undiluted samples, in samples diluted in 6 ml water or saliva, and in saliva-dentifrice slurries after 2 min brushing. The activity potentials were compared with the activities of NaF standards. The fluoride ion concentration of each dentifrice was determined when 0.1 g dentifrice was dissolved in 5 ml water and 20 ml buffer. The activities in diluted samples were about twice the activities in in vivo samples. The fluoride ion activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The measured values are relative, but observations are comparable [Birkeland, 1971] (a) The standard deviation by pipetting the original 7.0 ml fluid was 0.005 g (n=10), i.e. below 0.1%.…”
Section: Sdjoo Xmentioning
confidence: 67%
See 3 more Smart Citations
“…The measured values are relative, but observations are comparable [Birkeland, 1971] (a) The standard deviation by pipetting the original 7.0 ml fluid was 0.005 g (n=10), i.e. below 0.1%.…”
Section: Sdjoo Xmentioning
confidence: 67%
“…The electrode potential (mV) of the expectorates, without any pH and buffer adjustment, was measured during stirring. The measurements (in duplicate) were compared with the fluoride ion activities (ppm F") of stand ards at pH 6.4 (solutions of sodium fluoride [Orion,] diluted with deion ized water) [Birkeland, 1971], Amount of fluoride. The total fluoride ion concentrations of the fluids were determined (in duplicate) after pH and ionic strenght adjustment (Tisab, Orion 94-09-10A; 1.0 ml sample + 1.0 ml buffer).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the work of MCCANN (1968 a), the fluoride ion activity in saliva 10^-' mol/1 was used. Since then, it has been found that this value is a little too high and probably is closer to 10"" mol/1 (BIRKELAND 1971). A correction for this would not change the important relationship in this context.…”
Section: Discussionmentioning
confidence: 94%